Green-Solvent Processed Blade-Coating Organic Solar Cells with an Efficiency Approaching 19% Enabled by Alkyl-Tailored Acceptors - Bai, Hairui; Ma, Ruijie; Su, Wenyan; Peña, Top Archie Dela; Li, Tengfei; Tang, Lingxiao; Yang, Jie; Hu, Bin; Wang, Yilin; Bi, Zhaozhao; Su, Yueling; Wei, Qi; et al. (Nano-Micro Letters, 2023)
Power-conversion-efficiencies (PCEs) of organic solar cells (OSCs) in laboratory, normally processed by spin-coating technology with toxic halogenated solvents, have reached over 19%. However, there is usually a marked PCE drop when the blade-coating and/or green-solvents toward large-scale printing are used instead, which hampers the practical development of OSCs. Here, a new series of N-alkyl-tailored small molecule acceptors named YR-SeNF with a same molecular main backbone are developed by combining selenium-fused central-core and naphthalene-fused end-group. Thanks to the N-alkyl engineering, NIR-absorbing YR-SeNF series show different crystallinity, packing patterns, and miscibility with polymeric donor. The studies exhibit that the molecular packing, crystallinity, and vertical distribution of active layer morphologies are well optimized by introducing newly designed guest acceptor associated with tailored N-alkyl chains, providing the improved charge transfer dynamics and stability for the PM6:L8-BO:YR-SeNF-based OSCs. As a result, a record-high PCE approaching 19% is achieved in the blade-coating OSCs fabricated from a green-solvent o-xylene with high-boiling point. Notably, ternary OSCs offer robust operating stability under maximum-power-point tracking and well-keep > 80% of the initial PCEs for even over 400 h. Our alkyl-tailored guest acceptor strategy provides a unique approach to develop green-solvent and blade-coating processed high-efficiency and operating stable OSCs, which paves a way for industrial development. Highlights: 1 Alkyl-tailored Y-SMAs named YR-SeNF series with near-infrared absorption, different molecular crystallinity and self-assembly abilities are developed. 2 The related organic solar cells (OSCs) with an active layer processed from halogen-free solvents and spin-coating-free technologies achieve a 19% efficiency. 3 Ternary OSCs offer a robust operating stability under MPP tracking and well-keep > 80% of the initial efficiency for even over 400 h.